Methotrexate treatment strategies for rheumatoid arthritis: a scoping review on doses and administration routes - Esteban Rubio-Romero; César Díaz-Torné; María José Moreno-Martínez; Julen De-Luz (BMC Rheumatology, 2024)
Abstract Background To describe the evidence of methotrexate (MTX) initiation strategies in patients with rheumatoid arthritis (RA) and, in the case of non-responders, analyse the efficacy and safety of route and dose optimisation. Methods We conducted a comprehensive scoping review of randomised controlled trials according to PRISMA Scoping Reviews Checklist and the framework proposed by Arksey and O’Malley. PubMed, EMBASE, and Cochrane were searched without language restriction, and hand searches of relevant articles were examined. Results We identified 1,367 potentially eligible studies, of which 12 were selected based on the titles and abstracts and then on the full-length articles. In naïve-MTX patients, a linear dose-response relationship for starting dose was found between 5 mg/m2/week (7.5–10 mg/week) and 10 mg/m2/week (15–22 mg/week), without toxicity correlation. A higher initial dose of MTX (25 mg vs. 15 mg) was more effective, resulting in fewer dose increases due to ineffectiveness and more dose reductions due to higher remission rates. There was also a trend towards increased gastrointestinal toxicity. Comparing different routes of administration of MTX, subcutaneous MTX showed a statistically higher ACR20 response (85%) in comparison with oral MTX (77%) (p < 0.05). The clinical efficacy and safety of accelerated and conventional start MTX regimens were comparable between 7.5 and 15 mg with a 2,5 mg dose increase every two weeks. In RA patients who have failed the initial treatment with MTX, the stepwise increase in MTX doses is associated with a higher ACR20 response and sustained remission rate than other strategies. In MTX non-responders, optimisation to SC MTX was associated with improvements in ACR20 and ACR50 rates with similar toxicity between groups. In the early RA patients subgroup, SC MTX showed higher ACR20 response rates than oral MTX, and intensive oral methods have a much higher sustained remission rate, shorter mean time to remission, and better clinical disease activity measures than conventional treatments. Conclusions Higher starting doses of MTX and initial subcutaneous MTX made better performance in improving the ACR20 response, although the clinical effectiveness and safety of other MTX start regimens are comparable. This scoping review provides evidence in support of optimising MTX treatment in terms of route and dose prior to concluding that MTX treatment in RA patients has failed.